Caffeic Acid Inhibits Swelling, Bone Loss, and Osteoclastogenesis in Adjuvant-induced Arthritis Rats - Ferry Sandra; Muhammad Ihsan Rizal; Nurrani Mustika Dewi; Toshio Kukita (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Increase in inflammatory cytokine levels promotes pathological osteoclast differentiation. Caffeic acid has anti-inflammatory properties and can inhibit osteoclast bone resorption. In vitro studies have reported the ability of caffeic acid in inhibiting osteoclastogenesis pathways, however the in vivo study is rarely conducted. The aim of this study is to examine the role of caffeic acid in reducing inflammation and inhibiting osteoclastogenesis in Adjuvant-Induced Arthritis (AIA) rats.METHODS: Rats were injected with Freund’s Complete Adjuvant (CFA) and mineral oil. One day after injection, various concentration (0, 5, 25, 125 mg) of caffeic acid were given gastro-intestinally. Swelling degree in rats’ ankle joints was determined by measuring height and width of each ankle joint. Bone loss level was examined with soft X-ray, and then bone density was calculated. To examine osteoclastogenesis, ankle joints were stained with Tartrate-Resistant Acid Phosphatase (TRAP) and evaluated microscopically. RESULTS: Ankle joints of AIA rats had severe swelling before treated, yet the swelling was reduced based on concentration-dependent after receiving caffeic acid. Severe bone loss in AIA rats’ ankle joints were also observed, however the treatment of 125 mg caffeic acid showed remarkable inhibition effect toward rats’ bone loss. Osteoclastogenesis in AIA rats’ ankle joints were higher than the normal ones, as indicated with high TRAP-positive Multinucleated Cells (MNCs). But low number of TRAP-positive MNCs was observed in ankle joint of AIA rats that received 125 mg caffeic acid.CONCLUSION: Administration of caffeic acid can reduce the degree of swallowing, inhibit bone loss, and inhibit osteoclastogenesis in ankle joint of arthritis-induced rats.KEYWORDS: caffeic acid, osteoclastogenesis, bone loss, swelling, inflammation, RANKL, TNF-α